Associations between dietary patterns and longitudinal quality of life changes in colorectal cancer patients: the ColoCare study - Gigić, Biljana; Toth, Reka; Habermann, Nina; Scherer, Dominique; Schrotz-King, Petra; Abbenhardt-Martin, Clare; Brenner, Hermann; Chang-Claude, Jenny; Hoffmeister, Michael; Schneider, Martin; Ulrich, Alexis; Ulrich, Cornelia (Nutrition and cancer, 2018)
Quality of life (QoL) is an important clinical outcome in cancer patients. We investigated associations between dietary patterns and QoL changes in colorectal cancer (CRC) patients. The study included 192 CRC patients with available EORTC QLQ-C30 data before and 12 months post-surgery and food frequency questionnaire data at 12 months post-surgery. Principal component analysis was used to identify dietary patterns. Multivariate regression models assessed associations between dietary patterns and QoL changes over time. We identified four major dietary patterns: “Western” dietary pattern characterized by high consumption of potatoes, red and processed meat, poultry, and cakes, “fruit&vegetable” pattern: high intake of vegetables, fruits, vegetable oils, and soy products, “bread&butter” pattern: high intake of bread, butter and margarine, and “high-carb” pattern: high consumption of pasta, grains, nonalcoholic beverages, sauces and condiments. Patients following a “Western” diet had lower chances to improve in physical functioning (OR = 0.45 [0.21-0.99]), constipation (OR = 0.30 [0.13-0.72]) and diarrhea (OR: 0.44 [0.20-0.98]) over time. Patients following a “fruit&vegetable” diet showed improving diarrhea scores (OR: 2.52 [1.21-5.34]. A “Western” dietary pattern after surgery is inversely associated with QoL in CRC patients, whereas a diet rich in fruits and vegetables may be beneficial for patients' QoL over time.
Gesehen am 24.01.2018